Potential Solutions for Power System Impacts due to Power System Impacts due to Very Large Scale Photovoltaic (LACCEI, 2024)
Solar Photo Voltaic System (SPVS) is rapidly growing and decreasing PV panel prices, with great technology advances in inverter and controller design. The variable power generation and its non-dispatch of PV (photovoltaic cells) affects the reliability and stability of the power system (PS), causing voltage fluctuations, violation and unbalance [1]. Its high penetration at the transmission level affects the PS frequency more than the bus voltage-caused by cloud mispass. Available flexible options need to be considered to resolve and mitigate the impacts to the PS caused by high PV penetration.